2010
DOI: 10.1002/cncr.25128
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive expression of the polycomb group proteins Bmi1 polycomb ring finger oncogene and enhancer of zeste homolog 2 in nonsmall cell lung cancers and their clinical and clinicopathologic significance

Abstract: BACKGROUND:The polycomb group genes Bmi1 polycomb ring finger oncogene (Bmi1) and enhancer of zeste homolog 2 (EZH2) function as transcriptional repressors involved in gene silencing and in the malignant transformation and biologic aggressiveness of several human carcinomas. In the current study, the authors evaluated Bmi1 and EZH2 protein expression in specimens of human nonsmall cell lung cancer (NSCLC). METHODS: The authors conducted an immunohistochemical assessment of 157 surgically resected NSCLCs to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
56
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 46 publications
7
56
1
Order By: Relevance
“…28 EZH2 up-regulation reportedly promoted tumor growth both in vitro and in vivo, [13][14][15][16][17][18][19][20] and it is present in several cancers in the clinical setting, including melanoma, lymphoma, prostate cancer, and breast cancer. 29 It also has been demonstrated that EZH2 is useful as a potential biomarker to distinguish aggressive breast tumors from more benign tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 EZH2 up-regulation reportedly promoted tumor growth both in vitro and in vivo, [13][14][15][16][17][18][19][20] and it is present in several cancers in the clinical setting, including melanoma, lymphoma, prostate cancer, and breast cancer. 29 It also has been demonstrated that EZH2 is useful as a potential biomarker to distinguish aggressive breast tumors from more benign tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Recent studies have demonstrated that EZH2 is frequently overexpressed in several human epithelial cancer types, including prostate cancer, inflammatory breast cancer, gastric cancer, nonsmall cell lung cancer, esophageal cancer, salivary adenoid cystic carcinoma, recurrent nasopharyngeal carcinoma, and oral cancer, and it has been linked to a poor prognosis in patients with those cancers. [13][14][15][16][17][18][19][20] In addition, in our prior study, we observed that high EZH2 levels frequently were correlated with oral cancer development in patients with oral leukoplakia. 21 Together, the previous studies suggest that EZH2 may be a key oncoprotein involved in tumor initiation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, one group reported that Bmi-1 expression wasn't a significant prognostic factor, and was not correlated with any clinical pathological factors, only relative with early pathologic tumor classification in NSCLC. 11 Based on these controversial findings, further exploring the role of Bmi-1 in progression of lung cancer is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Deregulation of the EZH2-H3K27me3 pathway may also occur by other mechanisms, with over-expression of EZH2 associated with poor outcome in a range of solid tumours. [7][8][9] In this study, we set out to determine the prevalence and the prognostic value of EZH2 Y641 variants in a large cohort of patients with FL, and the relationship between mutation and EZH2 and H3K27me3 expression. Lymph node samples from 221 patients with FL were available from the tissue archive at St Barts and London Hospital (London Research Ethical Committee (05/Q0605/140)).…”
mentioning
confidence: 99%